(untitled) (Nigerian Journal of Technology, 2018)
In the deregulated power system, competition arises in generation and distribution but the transmission corridor remains the same for transferring power. Every operator wants to maximize profit, as such the number of transaction increases. This may cause congestion in transmission network. To avoid this, every operator should know the value of available transfer capability (ATC) before every transaction. Determination of ATC is a complex task which has to be done at periodic intervals for each source and sink pairs. Though there are many methods available to assess ATC, the most accurate method is repeated power flow using newton raphson (RPFNR). In this research work, RPFNR approach was applied on both 3-bus and 14 bus network by modeling and simulation using Power World Simulator (PWS). ATC between nodes and areas for both networks were determined. The error difference between ATC obtained from both procedures was negligible. A 14-bus system was further modeled, and ATC between nodes and areas were determined. http://dx.doi.org/10.4314/njt.v37i2.30